2020
DOI: 10.1002/joa3.12409
|View full text |Cite
|
Sign up to set email alerts
|

Weight, height, weight change, and risk of incident atrial fibrillation in middle‐aged men and women

Abstract: Background Anthropometric factors are reported to be risk factors for atrial fibrillation (AF), but it is unclear whether weight change in mid‐life is associated with AF. We aimed to study the possible associations of weight, height, and weight change with the risk of incident AF in men and women. Methods Our study cohort included 108 417 persons (51% women) who participated in a population‐based health examination in northern Sweden at 30, 40, 50, or 60 years of age. The health examination included weight and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…Fourth, the questionnaire used to collect data on several lifestyle factors has not been separately validated. On the other hand, several previous studies using the data from the same VIP health examinations have found associations between the recorded risk factors (e.g., studies regarding the association between alcohol consumption and risk of AF, and anthropometric factors and risk of AF) that are consistent with findings from other cohorts [40,41]. We also lack information on some conditions associated with both hyperglycemia and AF, for example, heart failure and obstructive sleep apnea [29,42,43], and we do not have information about the duration or severity of hypertension.…”
Section: Discussionsupporting
confidence: 81%
“…Fourth, the questionnaire used to collect data on several lifestyle factors has not been separately validated. On the other hand, several previous studies using the data from the same VIP health examinations have found associations between the recorded risk factors (e.g., studies regarding the association between alcohol consumption and risk of AF, and anthropometric factors and risk of AF) that are consistent with findings from other cohorts [40,41]. We also lack information on some conditions associated with both hyperglycemia and AF, for example, heart failure and obstructive sleep apnea [29,42,43], and we do not have information about the duration or severity of hypertension.…”
Section: Discussionsupporting
confidence: 81%
“…Greater height has been identified as a risk factor for AF in several studies [2,9,[62][63][64] and in both males [10,65] and females [65,66]. Some studies report that taller people have greater heart chamber size [9,10,63,65,66], meaning a larger left atrial size, which may be potential explanation albeit not a very robust one as AF is driven by left atrial stretch and fibrosis. Two other anthropometric traits, weight and waist circumference, ranked just below standing height.…”
Section: Af Resultsmentioning
confidence: 99%
“…Two other anthropometric traits, weight and waist circumference, ranked just below standing height. Obesity is associated with increased risk of left atrial enlargement, atrial fibrosis, electrical derangements of the atria, impaired diastolic function, inflammation and accumulation of pericardial fat, which are all key mechanisms in the pathogenesis of AF [10, 62, 65, 66]. The ranking of sex as the 7 th most significant feature in the model is also in agreement with epidemiological studies reporting sex differences in AF, males are at higher risk which is in agreement with our results, along with the electrophysiologic properties of the atria and structural remodelling[59, 60].…”
Section: Discussionmentioning
confidence: 99%
“…Large body size at a young age anticipated development of AF in further life. Higher BMI and BSA in adolescence are strongly related with AF in future [6]. Obesity is also associated with an increased risk of transition from paroxysmal AF to persistent AF.…”
Section: Predictors and Risk Factorsmentioning
confidence: 98%